Ayat Tentang Tujuan Pendidikan - Monitasaroh, Rizki Ayu (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
Each process which is done in education should be done with conscious andpurposeful. In Islam, the aim of Islamic education is making human who has noblecharacter (akhlakul karimah). Islamic educational goal is seen clearly as somethingthat is expected to be realized after experiencing the whole Islamic education, that aperson's personality that made him to be a perfect man. This means that the wholeof human spiritual and physical can live and develop natural and normal for itsobedience to Allah SWT. Thus, education can create the expected changes in thewhole world changes in human life as recorded in the Qur'an.